Les consoles de l’Éternité, à l’ombre des ordinateurs : Les Cordelettes de Browser de Tristan Garcia - Arnaud Despax (ReS Futurae, 2017)
Philosopher and novelist, Tristan Garcia provides in Les Cordelettes de Browser (2012) the strangely archaic image of unnamed computers : the characters of « Eternity » use smalls wood consoles to arrange reality, in order to maintain their whole life as eternal and be constantly comfortable. It seems therefore easy to compare this device with our times, and necessary to question why a vocabulary specific to computers is never employed. This contribution to a reflexion on computing imagination aims at seeing how these metaphors of computing immobilize that world in a way that shows regressive phantasms as well as totalitarian reductions. Against such temptations, the book insists on the fact that matter is fundamental and claims a consolatory and relational purpose ; thus word games take part in the opening of a meaning that confirms that man belongs to an organic nature as well as he needs to part from it.